Reconceptualising Behavioral and Psychological Symptoms of Dementia: Views of People Living With Dementia and Families/Care Partners - Burley, Claire V.; Casey, Anne-Nicole; Chenoweth, Lynn; Brodaty, Henry (Frontiers in Psychiatry, 2021)
Background: Behavioral and psychological symptoms of dementia (BPSD, also known as neuropsychiatric symptoms (NPS), changed behaviors and responsive behaviors), occur in up to 90 per cent of people living with dementia (PLWD). These symptoms and behaviors strongly correlate with functional and cognitive impairment and contribute to approximately 30 per cent of overall dementia costs. As decisions regarding care and strategies for BPSD are generally based on professional frames of reference, this study investigates whether the perspectives of PLWD and families/care partner on BPSD terminology can inform a more nuanced conceptualization of BPSD. Methods: PLWD and families/care partners participated in one-on-one semi-structured interviews. A thematic iterative approach was used to code the data and identify common themes until theoretical saturation was reached. Themes were compared between groups. Data were analyzed deductively in relation to pre-existing terminology regarding BPSD, and inductively to discover new ideas on use of such terminology as perceived by PLWD and others. Results: Forty-one volunteers were interviewed: 21 PLWD, mean age 71yrs, mean Mini-Mental State Examination score 25, and 20 family members/care partners. Three main themes emerged from the data: (1) descriptions of BPSD from people with lived experience compared to clinical terms, (2) viewpoints on interpreting causes, and (3) experiences of concurrent BPSD. The experiences described and terms used by PLWD and families/ care partners differed from terms used in existing professional frameworks (e.g., ‘disinhibition’ described as ‘loss of filter’) and there were differences between PLWD and family members’ interpretations of BPSD causes. Discussion/ Conclusion: Reports from PLWD and families/carers describing their experiences of BPSD suggest a reconceptualization of BPSD terminology is needed to understand and de-stigmatize these symptoms and behaviors. For example, the term ‘agitated/ hard to handle’ would benefit by clearer, contextualized description, such as ‘frustrated with cognitive decline, discriminatory behavior and inadequate support systems.’ In better understanding individual expressions of BPSD, families, professionals and societies will be able to respond in ways that are helpful for PLWD. An informed, integrated understanding of BPSD and improved terminology use will have the potential to improve the quality of care and support for PLWD.